Digital teaching materials for illustrated folklore of the archipelago with character values for Elementary/MI students - Hariyani Hariyani; Yusida Gloriani; Jimat Susilo (Kantor Bahasa Provinsi Banten and Perkumpulan pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya (PPJB-SIP)., 2025)
This research aims to develop digital teaching materials for illustrated archipelago folklore containing character values for elementary/MI students. The steps of this research consist of, needs analysis, designing digital teaching materials for illustrated Nusantara folklore that contain character values, development of illustrated Nusantara folklore digital teaching materials containing character values, implementation of illustrated Nusantara folklore digital teaching materials products containing character values, and evaluation of illustrated Nusantara folklore digital teaching materials containing character values. Data collection in this study involved gathering data from validation questionnaires completed by material and language experts, media experts, practitioners, and those involved in the implementation of learning. The data acquisition was analyzed in a descriptive analysis using the Likert scale and the Paired Sample T-Test. The results of the validation test by material and language experts obtained a score of 3.17; the validation test by media experts obtained a score of 3.65; validation test by Indonesian teachers obtained a score of 3.65; The results of the implementation of illustrated Nusantara folklore digital teaching materials containing character values for elementary/MI students received a positive response from students by obtaining a score of 3.63. The conclusion of this study shows that overall, this study proves that the development of digital teaching materials for illustrated archipelago folklore loaded with character values can answer the needs of students and has a positive impact on the learning process and outcomes in grade V SD/MI.